Alles geht? Die jüngste Geschichte der „sozialen Medien“. Zwischen Wirtschaft und Gemeinschaft - Schmitt, Martin (Soziale Medien – wie sie wurden, was sie sind)
Twitter ist jetzt X und befindet sich auf dem absteigenden Ast. Auf diesem Ast sitzt Facebook bereits seit längerem. Der Kurzvideodienst Vine, Vorgänger von TikTok, ist Geschichte. Und auch bei Google klingeln die Alarmglocken angesichts der „neuen“ Konkurrenz durch Microsoft und ChatGPT. Umso dringlicher wird also die Historisierung der „sozialen Medien“, das heißt, sie in ihren historischen Kontext einzuordnen und ihren Mythos zu entzaubern. Dabei wartet das Vorhaben mit einer doppelten Herausforderung auf: Erstens, dass es sich bei den Unternehmen der Branche und zweitens auch bei den dort gebildeten Gemeinschaften um recht flüchtige, wandelhaften Gestalten handelt. Scheitern und Wandel ist Teil der „sozialen Medien“ – und sei es nur in der schnellen Abfolge der Moden des „nächsten großen Dings“. Dementsprechend versucht dieser Beitrag mit einem systematischeren Ansatz als dem der gesellschaftlichen Selbstbeschreibung, die Entwicklung des sozio-digitalen Phänomens „soziale Medien“ in dessen Zeitkontext einzuordnen.
Keywords: Digitalgeschichte; Soziale Medien; Technikgeschichte; Wirtschaftsgeschichte; Digitalisierung; Twitter; Facebook; Meta

Interview Study on Strategy Options for Platform Operation in B2B Markets - Özcan, Leon; Fichtler, Timm; Kasten, Benjamin; Koldewey, Christian; Dumitrescu, Roman
Keywords: Digital Platform; Platform Strategy; Strategic Management; Platform Life Cycle; Interview Study; Business Model; Business-to-Business; Two-sided Market; Multi-sided Market

Evaluation Criteria in Product Idea Selection Decisions - Gräßler, Iris; Koch, Anna-Sophie (XXXIII Proceedings of the ISPIM Innovation Conference)
Within innovation management, choosing the best fitting product idea is the most important decision point. The future existence and success of the organization is depending on selected product ideas. To find the best fitting idea for an organization, it needs evaluation criteria representing the organizations mission Therefore, this study focuses on a holistic overview about evaluation criteria and on supporting organizations in the process to select its individual evaluation criteria. Based on a literature study, existing approaches regarding evaluation criteria in product idea selection are identified and a list of evaluation criteria is reworked. Using the list of evaluation criteria, a prioritization method is created. Within an interview with experts in innovation management, the method is discussed regarding usability and the level of assistance in product idea selection. The developed criteria can be used directly by innovation manager and industrial practitioners to evaluate potential product ideas.
Keywords: innovation management; evaluation criteria; idea selection; idea evaluation; meta-study

Curricular integration of academic and vocational education: a theory-based empirical typology of dual study programmes in Germany - Mordhorst, Lisa; Jenert, Tobias (Higher Education)
In Germany, dual learning programmes are increasingly offered by higher education institutions. These programmes’ main characteristic and greatest challenge is their integration of academic and vocational learning. So far, this challenge has frequently been stated without specifying its exact nature and consequences for learners. The present study addresses this pedagogical research gap and examines the extent of variation in the degree of integration among dual study programmes. With reference to curriculum theory, the study develops an empirical typology of curricular integration in dual programmes. The data sample consists of 152 programmes at (dual) universities and universities of applied sciences. Data is analysed using hierarchical cluster analysis. Results indicate that the currently prevailing forms of curricular integration should best be differentiated according to five types. The five overlapping types of integration are located on a continuum ranging from parallelism through organisational linking to full curricular integration targeted immediately at students’ personal integration. The analysis confirms that there are problems with complying with integration standards set on the policy level. Above all, the study offers new insights on what marks the diverse integration landscape of dual study programmes. It proves that approaches to integration are more differentiated than previous research has shown.
Keywords: Dual study programmes · Curricular integration · Curriculum theory · Empirical typology · Cluster analysis · Germany

Supporting Innovation Management for SMEs: A Tool for Idea Selection - Gräßler, Iris; Koch, Anna-Sophie; Thiele, Henrik; Dattner, Michael (Proceedings of the ISPIM Innovation Conference)
In innovation management, usually there is a large number of product ideas, not all of which meet the requirements of a company and make sense to pursue further. For selecting the most promising ideas, several methods exist which each focus on a certain aspect. Due to the characteristics of Small and Medium Enterprises (SMEs) such as limited resources, these enterprises have special requirements on methods for selecting ideas. In this study, criteria of SMEs for idea selection are deducted from SME-characteristics. Methods for idea selection are tested for fulfillment of these criteria and the results are combined in a matrix. Together with a guideline, a tool for idea selection in innovation management of SMEs is developed. The results are validated in the context of innovation management in SMEs. By selecting a method, a SME is enabled to make economically viable decisions for their product portfolio, thus ensuring sustainable economic success.
Keywords: innovation management; SME; evaluation method; idea selection; meta-study; idea evaluation

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England and several countries in Continental Europe we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance of maintaining good physical health in old age for cognitive functioning.
Keywords: Cognitive decline; health shocks; retirement; education; event study

The dynamic and heterogeneous effects of retirement on cognitive decline - Schmitz, Hendrik; Westphal, Matthias
We study effects of retirement on cognitive abilities (up to ten years after retirement) using data from 21 countries in Continental Europe, England, and the US, and exploiting early-retirement thresholds for identification. For this purpose, combines event-study estimations with the marginal treatment effect framework to allow for effect heterogeneity. This helps to decompose event-study estimates into true medium-run effects of retirement and effects driven by differential retirement preferences. Our results suggest considerable negative effects of retirement on cognitive abilities. We also detect substantial effect heterogeneity: Those who retire as early as possible are not affected while those who retire later exhibit negative effects.
Keywords: Cognitive abilities; retirement; event study; marginal treatment effects

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Share Price Reactions to Tariﬀ Imposition Announcements in the Trump Era – an Event Study of the Trade Conﬂict - Wengerek, Sascha Tobias; Uhde, André
Employing a unique sample of 2,849 tariﬀ imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariﬀ announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariﬀ announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariﬀ impositions, e.g. a decrease in the companies’ future cash ﬂows and a threat of retaliation. The negative wealth eﬀects are observed irrespective of whether the Trump administration announces safeguard tariﬀs to protect domestic ﬁrms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we ﬁnd that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariﬀ, trade and ﬁrm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariﬀs; trade conﬂict

Share price reactions to tariff imposition announcements in the Trump era - An event study of the trade conflict - Wengerek, Sascha Tobias
Employing a unique sample of 2,849 tariff imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariff announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariff announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariff impositions, e.g. a decrease in the companies' future cash flows and a threat of retaliation. The negative wealth effects are observed irrespective of whether the Trump administration announces safeguard tariffs to protect domestic firms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we find that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariff, trade and firm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariffs; trade conflict

Timing in Information Security: An Event Study on the Impact of Information Security Investment Announcements - Szubartowicz, Eva; Schryen, Guido (Journal of Information System Security)
Timing plays a crucial role in the context of information security investments. We regard timing in two dimensions, namely the time of announcement in relation to the time of investment and the time of announcement in relation to the time of a fundamental security incident. The financial value of information security investments is assessed by examining the relationship between the investment announcements and their stock market reaction focusing on the two time dimensions. Using an event study methodology, we found that both dimensions influence the stock market return of the investing organization. Our results indicate that (1) after fundamental security incidents in a given industry, the stock price will react more positively to a firm’s announcement of actual information security investments than to announcements of the intention to invest; (2) the stock price will react more positively to a firm’s announcements of the intention to invest after the fundamental security incident compared to before; and (3) the stock price will react more positively to a firm’s announcements of actual information security investments after the fundamental security incident compared to before. Overall, the lowest abnormal return can be expected when the intention to invest is announced before a fundamental information security incident and the highest return when actual investing after a fundamental information security incident in the respective industry.
Keywords: Event Study; Information Security; Investment Announcements; Stock Price Reaction; Value of Information Security Investments

Anforderungen an Studienordnungen in einer digital vernetzten Welt - Caruso, Carina; Martin, Alexander (Zeitschrift für Hochschulentwicklung)
Der Beitrag widmet sich der Frage, wie lehrer*innenbildende Hochschulen der Digitalisierung auf der Ebene der Überarbeitung und Anpassung von Studienordnungen begegnen können. Ziel des interdisziplinären Vorhabens ist es, ausgehend von einer Inhaltsanalyse nordrhein-westfälischer Studienordnungen einen Kriterien- bzw. Fragenkatalog zu entwickeln, der diejenigen bildungspolitischen Vorgaben zur Verankerung digitaler Kompetenz fasst, die künftigen Akkreditierungen von Studiengängen zugrunde liegen werden und der fach- und standortübergreifend eingesetzt werden kann.
Keywords: Studienordnungen; Digitalisierung; Lehrer*innenbildung; Professionalisierung / study regulations; digitalisation; teacher training; professionalisation

Extending Loyalty Programs with BI Functionalities A Case Study for Brick-and-Mortar Stores - Kucklick, Jan-Peter; Kamm, Michael Reiner; Schneider, Johannes; vom Brocke, Jan (Proceedings of the 53rd Hawaii International Conference on System Sciences)
Effective customer loyalty programs are essential for every company. Small and medium sized brick-and- mortar stores, such as bakeries, butcher and flower shops, often share a common overarching loyalty program, organized by a third-party provider. Furthermore, these small shops have limited resources and often cannot afford complex BI tools. Out of these reasons we investigated how traditional brick-and- mortar stores can benefit from an expansion of service functionalities of a loyalty card provider. To answer this question, we cooperated with a cross-industry customer loyalty program in a polycentric region. The loyalty program was transformed from simple card-based solution to a mobile app for customers and a web- application for shop owners. The new solution offers additional BI services for performing data analytics and strengthening the position of brick-and-mortar stores. Participating shops can work together in order to increase sales and align marketing campaigns. Therefore, shopping data from 12 years, 55 shops, and 19,000 customers was analyzed.
Keywords: brick-and-mortar stores; business intelligence; case study; loyalty program

Data mining for small shops: Empowering brick-and-mortar stores through BI functionalities of a loyalty program1 - Kamm, Michael Reiner; Kucklick, Jan-Peter; Schneider, Johannes; vom Brocke, Jan (Information Systems Management)
While the analysis and usage of data are increasing in importance, the application of sophisticated BI solutions in small stores is limited by available technical capabilities and financial resources. This study investigates how brick-and-mortar stores can benefit from an expansion of service functionalities of a cross-industry loyalty card provider. Digitalizing the loyalty program created new opportunities, while the analysis of shopping data of 13 years, 19,000 customers, and 55 shops empowered data-based decision support.
Keywords: Customer loyalty; case study; brick-and-mortar stores; business intelligence; loyalty programs

Dual Study Programmes as a Design Challenge: Identifying Areas for Improvement as a Starting Point for Interventions - Mordhorst, Lisa; Gössling, Bernd (EDeR. Educational Design Research)
The proportion of freshmen enrolled in dual study programmes has steadily increased in recent years. From the perspective of potential students, these programmes are highly attractive because they combine types of learning that used to be largely separate at an institutional level: vocational and academic learning. In training-integrated dual study programmes, different institutional contexts, governance regimes, teaching styles and learning environments make bridging these two worlds of learning a challenge for both educators and learners. However, these programmes also allow leeway for didactic innovation, through the cooperation of different types of educational institutions and through new ways of using available didactic methods, and for establishing a new relationship between higher education (HE) and vocational education and training (VET). This paper positions training-integrated dual study programmes as an object of design-based research (DBR). By developing and using an extended model for the pedagogic development of HEIs, “pädagogische Hochschulentwicklung” (Brahm, Jenert, & Euler, 2016a, p. 19; Euler, 2013, p. 360), the paper systematically identifies generic educational problems in these hybrids. Based on a literature review, this paper classifies and explains the design challenges at the level of the learning environment, the study programme and the organisation. The challenges revolve mainly around the cooperation and integration of HE and VET. The paper concludes with an outlook on future DBR projects designing dual studies.
Keywords: Dual study programmes; Design challenges; Pedagogic development of HEIs; Literature review; Study programme development; DBR cycle

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS spread changes - Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We find that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric five-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline finding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Share price reactions to tariff imposition announcements in the Trump era – An event study of the trade conflict - Wengerek, Sascha Tobias; Uhde, André
Employing a unique sample of 2,849 tariff imposition announcements by and against the United States (U.S.) over the period from 2018 to 2019, this study analyzes the impact of recent tariff announcements on share prices from 859 U.S. companies. We provide evidence for negative (cumulative) average abnormal stock returns due to tariff announcements during a symmetric three-day event window. We suggest that stock market investors expect adverse impacts of tariff impositions, e.g. a decrease in the companies' future cash flows and a threat of retaliation. The negative wealth effects are observed irrespective of whether the Trump administration announces safeguard tariffs to protect domestic firms or a retaliation is declared by foreign countries. Moreover, building several subsamples, we find that the adverse impact is mostly driven by announcements involving China and is associated with a variety of sector, tariff, trade and firm characteristics.
Keywords: event study; international relations; protectionism; strategic trade policy; tariffs; trade conflict

The relationship between announcements of complete mergers and acquisitions and acquirers' abnormal CDS-Spread changes - Uhde, André; Hippert, Benjamin
Employing a sample of 492 merger and acquisition (M&A) announcements from 284 acquirers across North America and Europe between 2005 and 2018, this study analyzes the impact of M&A announcements on an acquirers abnormal CDS spread changes. We nd that spreads from CDS which are written on acquirers increase by 310 bps during a symmetric ve-day event window suggesting that investors expect an increase in the acquirers credit risk exposure due to M&As. Next to this baseline nding, we conduct a large variety of sensitivity analyses to gain more insight into the driving factors of the rising risk perception of CDS investors due to M&A announcements.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Information Security Investments: An Exploratory Multiple Case Study on Decision-Making, Evaluation and Learning - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (Computers & Security)
The need to protect resources against attackers is reflected by huge information security investments of firms worldwide. In the presence of budget constraints and a diverse set of assets to protect, organizations have to decide in which IT security measures to invest, how to evaluate those investment decisions, and how to learn from past decisions to optimize future security investment actions. While the academic literature has provided valuable insights into these issues, there is a lack of empirical contributions. To address this lack, we conduct a theory-based exploratory multiple case study. Our case study reveals that (1) firms? investments in information security are largely driven by external environmental and industry-related factors, (2) firms do not implement standardized decision processes, (3) the security process is perceived to impact the business process in a disturbing way, (4) both the implementation of evaluation processes and the application of metrics are hardly existent and (5) learning activities mainly occur at an ad-hoc basis.
Keywords: Information Security Investments; Multiple Case Study; Organizations; Single Loop Learning; Double Loop Learning

“As a person, I feel I’ve changed pretty immensely”: Sojourners’ aspirations and self-perceived achievements - Müller, Mareike (The Canadian Modern Language Review)
This article explores the interplay between learners’ linguistic and personal objectives as well as evaluations of their achievements in study-abroad contexts, an area that has thus far remained widely unexplored given the prevalence of product-oriented, outcomes-based research. The study draws on the case of one Canadian student of German who studied abroad at a German university for one year. To adopt an emic perspective, the data gained from a learning history questionnaire, semi-structured interviews, and e-journals were analyzed and interpreted within the framework of narrative analysis. The results show not only that learners’ sojourn objectives may be complex, dynamic, and contradictory in nature but also that they need to be examined beyond their face value, as they are entangled with learners’ negotiations of desirable subject positions and attempts to integrate their sojourn experiences, successes, and frustrations in a coherent and positive life narrative.
Keywords: individual differences; learner beliefs; narrative analysis; sojourn objectives and evaluations; study abroad